An Automated Fluorescence-Based Method to Isolate Bone Marrow-Derived Plasma Cells from Rhesus Macaques Using SIVmac239 SOSIP.664 - Nuria Pedreño-Lopez (Molecular Therapy: Methods & Clinical Development, 2020)
Simian immunodeficiency virus (SIV) infection of Indian rhesus macaques (RMs) is one of the best-characterized animal models for human immunodeficiency virus (HIV) infection. Monoclonal antibodies (mAbs) have shown promise for prevention and treatment of HIV infection. However, it has been difficult to isolate mAbs that potently neutralize the highly pathogenic SIVmac239 strain. This has been largely due to the low frequency of circulating B cells encoding neutralizing Abs. Here we describe a novel technique to isolate mAbs directly from bone marrow-derived, Ab-secreting plasma cells. We employed an automated micromanipulator to isolate single SIVmac239 SOSIP.664-specific plasma cells from the bone marrow of a SIVmac239-infected RM with serum neutralization titers against SIVmac239. After picking plasma cells, we obtained 44 paired Ab sequences. Ten of these mAbs were SIV specific. Although none of these mAbs neutralized SIVmac239, three mAbs completely neutralized the related SIVmac316 strain. The majority of these mAbs bound to primary rhesus CD4+ T cells infected with SIVmac239 and induced Ab-dependent cellular cytotoxicity. This method is a first step in successful isolation of antigen-specific bone marrow-derived plasma cells from RMs.